A Multilayered Magnetoelectric Transmitter with Suppressed Nonlinearity for Portable VLF Communication - Zhaoqiang Chu; Zhineng Mao; Kaixin Song; Shizhan Jiang; Shugang Min; Wei Dan; Chenyuan Yu; Meiyu Wu; Yinghui Ren; Zhichao Lu; Jie Jiao; Tianxiang Nan; et al. (Research, 2023)
Acoustically actuated magnetoelectric (ME) antenna based on the efficient oscillation of magnetic dipoles has recently been considered as a promising solution for portable very-low-frequency communications. However, the severe nonlinear dynamic behavior in the case of strong-field excitation results in insufficient radiation capability and poor communication performance for a conventional ME antenna. In this work, we propose to suppress the nonlinearity of an ME antenna by neutralizing the spring-hardening effect in amorphous Metglas and the spring-softening effect in piezoelectric ceramics through an ME multilayered transmitter (ME-MLTx) design. With a driving voltage of 50 Vpp at the resonance frequency of 21.2 kHz, a magnetic flux density as high as 108 fT at a distance of 100 m is produced from a single ME-MLTx. In addition, ME-MLTx performs a decreased mechanical quality factor (Q m) less than 40.65, and, thus, a broadened bandwidth of 500 Hz is generated. Finally, a communication link transmitting binary American Standard Code for Information Interchange-coded message is built, which allows for an error-free communication with a distance of 18 m and a data rate of 300 bit/s in the presence of heavy environment noise. The communication distance can be further estimated over 100 m when using a femtotesla-class-inductive magnetic field receiver. The obtained results are believed to bring ME antennas one step closer to being applicable in very-low-frequency communications.